Pentingnya Fungsi Manajemen Make Up Artist dalam Promosi melalui Pemasaran Digital - Aida Salwa Evelyna; Arvy Rizqia Ardana; Melinda Lailatus Zahro; Silfa Ratna Dita; Sri Endah Wahyuningsih (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Management plays a crucial role in supporting the effective promotion of Make-Up Artist (MUA) services amidst increasingly competitive digital marketing. This study aims to examine the importance of management functions in enhancing the effectiveness of MUA service promotion through digital marketing. The method used was a literature review, reviewing various scientific sources, such as books, journals, research articles, and other relevant references. The results of the study indicate that the implementation of management functions, including planning, organizing, implementing, and monitoring, contributes to the success of digital promotion strategies. Optimizing digital media through content management, strengthening personal branding, utilizing social media, and implementing appropriate pricing strategies are factors that support the competitiveness of MUA businesses. These findings indicate that strategically integrating management and digital marketing functions can increase promotional effectiveness and expand market reach for MUA businesses in the digital era.